Hypoglycaemia in anesthesiology practice: Diagnostic, preventive, and management strategies - Kalra, Sanjay (Medknow Publications & Media Pvt Ltd, 2013)
Diabetes mellitus has emerged as one of the fastest growing non communicable diseases worldwide. Management of diabetic patients during surgical and critically illness is of paramount challenge to anesthesiologist and intensivist. Among its major acute complications, hypoglycemia has been given lesser attention as compared to other major acute complications; diabetic ketoacidosis and hyperosmolar non ketotic coma. However, newer studies and literary evidence have established the serious concerns of morbidity and mortality, both long- and short-term, related to hypoglycemia. basis. Invariably, diabetic patients are encountered in our daily routine practice of anesthesia. During fasting status as well as the perioperative period, it is hypoglycemia that is of high concern to anesthesiologist. Management has to be based on clinical, pharmacological, social, and psychological basis, so as to completely prevent the complications arising from an acute episode of hypoglycemia. This review aims to highlight various aspects of hypoglycemia and its management both from endocrine and anesthesia perspective.